2019
DOI: 10.4102/hsag.v24i0.1103
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of student nurses regarding the bursary system in KwaZulu-Natal province, South Africa

Abstract: Background: During 2010, the South African nursing education system was restructured, changing student nurses from having supernumerary status to being bursary holders. Changes with the introduction of this new bursary system included institutional factors and benefits that could be removed from the students, potentially hampering students’ sense of belonging.Aim: This study aimed to describe the experiences of students receiving bursaries in KwaZulu-Natal (KZN) province and to make recommendations for improvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Results revealed that most participants disagreed that financial counselling was available. Many studies reveal that non-academic challenges like finances negatively impact academic success and vice versa (Buthelezi, 2019;Jacobs et al, 2019;Mhlongo & Masango 2020;Zulu & Mutereko, 2020). Overall, the results showed a significant relationship between student support and academic success, evidenced by a p-value of < .05.…”
Section: Engagement Phase Supportmentioning
confidence: 80%
“…Results revealed that most participants disagreed that financial counselling was available. Many studies reveal that non-academic challenges like finances negatively impact academic success and vice versa (Buthelezi, 2019;Jacobs et al, 2019;Mhlongo & Masango 2020;Zulu & Mutereko, 2020). Overall, the results showed a significant relationship between student support and academic success, evidenced by a p-value of < .05.…”
Section: Engagement Phase Supportmentioning
confidence: 80%
“…In Zimbabwe, pregnant student nurses may also take longer to complete their studies because of a policy that instructs school principals to exclude pregnant students who, because of pregnancy-related physical discomfort, are facing academic challenges (Van Den Berg & Mamhute 2013:305). At the KwaZulu-Natal College of Nursing (KZNCN), the introduction of a new bursary system meant that pregnant student nurses forfeited their maternity benefits for a period of 6 months as they were not officially allowed to fall pregnant during their training (Jacobs 2014:55).…”
Section: Introductionmentioning
confidence: 99%